2006
DOI: 10.1103/physrevb.73.205331
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling emission from self-organized In(Ga)As∕GaAs quantum dots observed via time-resolved capacitance measurements

Abstract: The observation of tunneling emission of electrons and holes from In͑Ga͒As/ GaAs quantum dots in timeresolved capacitance measurements is reported. The electron and hole ground-state localization energies are determined as ͑290± 30͒ meV and ͑210± 20͒ meV, respectively. These energies are in excellent agreement with predictions from eight-band k · p theory. Based on the localization energies, we estimate the escape time for thermal excitation at room temperature as ϳ200 ns for electrons and ϳ0.5 ns for holes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 33 publications
1
34
1
Order By: Relevance
“…In this paper we report on a second, slow and temperature-independent emission component, observed in DLTS spectra of Co-and Cr-implanted Ge. Its spectral characteristics are similar to those of a parallel carrier emission path reported for quantum wells and dots in III-V semiconductors [12][13][14][15][16][17][18][19] that was assigned to direct, through barrier tunnelling. The hole emission component reported here is, however, much slower and only becomes apparent in the spectrum when recording transients with large observer window time (t W ).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this paper we report on a second, slow and temperature-independent emission component, observed in DLTS spectra of Co-and Cr-implanted Ge. Its spectral characteristics are similar to those of a parallel carrier emission path reported for quantum wells and dots in III-V semiconductors [12][13][14][15][16][17][18][19] that was assigned to direct, through barrier tunnelling. The hole emission component reported here is, however, much slower and only becomes apparent in the spectrum when recording transients with large observer window time (t W ).…”
Section: Introductionsupporting
confidence: 58%
“…In the DLTS spectra of certain quantum wells and dots a similar low-temperature non-thermal emission component has been observed and explained as the result of direct tunneling of a carrier out of the quantum well. [12][13][14][15][16][17][18][19] Other tunneling mechanisms that have been proposed for carriers out of defects or quantum wells, in particular phonon-and thermally assisted tunneling, are essentially thermally activated processes and cannot explain the current observations. In the case of direct tunneling, a strong dependence of τ c on electric field is expected, as the field determines the width of the tunnel barrier and it may in addition lower the barrier height for attractive centers (Poole-Frenkel effect).…”
Section: Origin Of the Non-thermal Emissioncontrasting
confidence: 47%
“…Electrical and optical properties of such heterostructures therefore become dependent on the ideality of the InGaAs/GaAs interfaces, and their description should take into account a realistic influence of the interface states as well as the quantum confined states. 10 It has been shown that InGaAs QD heterostructures contain defects with deep levels in the bandgap of GaAs that result from strain and In content variation in the interface transition layer. In general, such defects are thought to be potential traps as well as recombination and scattering centers for charge carriers, which in principle limit practical application of these nanostructures.…”
mentioning
confidence: 99%
“…However, a broad spectrum of electronic interface states has been revealed by admittance spectroscopy, deep-level transient spectroscopy (DLTS), and capacitance-voltage measurements. [10][11][12] Point defects tend to form in GaAs due to strain near the interfaces with InGaAs QDs. The concentration of these point defects strongly depends on the growth rate and temperature.…”
mentioning
confidence: 99%
“…Then at low temperature range, where the emission is not thermally activated, again a series of the Laplace DLTS spectra have been measured at different sample biases and, as a result, electric fields, and this gave the electric field dependence of the hole emission at temperatures where the thermal emission process is not contributing to the overall emission. For the tunnelling emission a simple triangle energy barrier model has been applied [14]. In this model the logarithm of the emission rate should linearly depend on the inverse of the electric field according to the formula…”
Section: Resultsmentioning
confidence: 99%